Comparison of femoral strength and fracture risk index derived from DXA-based finite element analysis for stratifying hip fracture risk: A cross-sectional study - Yang, Shuman; Luo, Yunhua; Yang, Lang; Dall'Ara, Enrico; Eastell, Richard; Goertzen, Andrew L.; McCloskey, Eugene V.; Leslie, William D.; Lix, Lisa M. (Bone (New York, N.Y.), 2018)
Dual-energy X-ray absorptiometry (DXA)-based finite element analysis (FEA) has been studied for assessment of hip fracture risk. Femoral strength (FS) is the maximum force that the femur can sustain before its weakest region reaches the yielding limit. Fracture risk index (FRI), which also considers subject-specific impact force, is defined as the ratio of von Mises stress induced by a sideways fall to the bone yield stress over the proximal femur. We compared risk stratification for prior hip fracture using FS and FRI derived from DXA-based FEA. The study cohort included women aged ≥65years undergoing baseline hip DXA, with femoral neck T-scores <−1 and no osteoporosis treatment; 324 cases had prior hip fracture and 655 controls had no prior fracture. Using anonymized DXA hip scans, we measured FS and FRI. Separate multivariable logistic regression models were used to estimate odds ratios (ORs), c-statistics and their 95% confidence intervals (95% CIs) for the association of hip fracture with FS and FRI. Increased hip fracture risk was associated with lower FS (OR per SD 1.36, 95% CI: 1.15, 1.62) and higher FRI (OR per SD 1.99, 95% CI: 1.63, 2.43) after adjusting for Fracture Risk Assessment Tool (FRAX) hip fracture probability computed with bone mineral density (BMD). The c-statistic for the model containing FS (0.69; 95% CI: 0.65, 0.72) was lower than the c-statistic for the model with FRI (0.77; 95% CI: 0.74, 0.80) or femoral neck BMD (0.74; 95% CI: 0.71, 0.77; all P<0.05). FS and FRI were independently associated with hip fracture, but there were differences in performance characteristics. •Lower femoral strength is associated with increased hip fracture risk.•High fracture risk index for the proximal femur is a risk factor for hip fracture.•Fracture risk index considers both femoral strength and fall-induced impact force.